Histiocytosis from Langerhans Cells with Isolated Lung Injury in a 3-year-old Child - A. V Glushkov; O. I. Andriyanova; F. K. Manerov; Yu. Yu. Merkulov; A. A. Loktionov (Общая реаниматология)
Histiocytosis from Langerhans cells with isolated lung injury is described in a 3-year-old child. The data available in the literature on the incidence and mechanisms of pathogenesis and the disease are given. Key words: histiocytosis from Langerhans cells.